OPTIMALISASI FUNGSI KAMERATERINTEGRASI MELALUI SOFTWARE STREAMING - Agung, I Putu Suhada (Capture : Jurnal Seni Media Rekam, 2016)
Notebook and Netbook contain several peripherals such us interface audio in/out, portLAN, WiFi, Port USB and the integrated camera (WebCam). WebCam can be used forteleconference through GoogleTalk, Skype andYahoo Messenger. But, the facilities of streamingare the scarcest benefit of WebCam as a CCTV application of digital software. In addition, tooptimize the integrated camera, it is needed some choices to find the appropriate things, theyare comparing streaming software,observing the same objects,recording for one minutes,andlive broadcasted. Therefore, the results of observation show that Unreal Live Server hasexcellence capabilities, because it has faster streaming , the password facilities, authentication,and blocking access.Keywords:Interface,webcam,teleconference,and streaming